Urine Biomarkers of Tubular Injury Predict Outcomes in Diabetic Nephropathy: A Prospective Cohort Study - Suwannathot, Atit; Satirapoj, Bancha; Supasyndh, Ouppatham; Nata, Naowanit (Journal of the Nephrology Society of Thailand, 2024)
Background: Currently available biomarkers, such as serum creatinine and albuminuria, exhibit low sensitivity in predicting renal progression. Novel biomarkers of tubular injury may aid in identifying patients with type 2 diabetes mellitus (T2DM) at high risk for renal progression. This study evaluates the potential of urine biomarkers of tubular damage in predicting renal progression and the composite outcome of renal progression and death in T2DM. Methods: This prospective cohort study involved 257 patients with T2DM. Urine biomarkers of tubular injury were assessed at baseline. The outcomes examined were the composite renal outcome of end-stage kidney disease (ESKD), a 40% decline in eGFR, and death. Results: Most patients were in chronic kidney disease (CKD) stages 3 and 4, with a median urine albumin/creatinine ratio of 60.8 mg/g. The median follow-up duration was 7 years. Baseline urine concentrations of cystatin-C, angiotensinogen, kidney injury molecule-1 (KIM-1), and neutrophil-gelatinase associated lipocalin (NGAL) were significantly higher among patients who reached the composite renal outcome. All tubular biomarkers demonstrated intermediate predictive performance for the composite renal outcome, with area under the curve (AUC) values ranging between 0.65 and 0.72, comparable to urine albumin/creatinine. Using the optimal cut-off value for each urine biomarker, higher levels were significantly associated with the composite renal outcome. However, when employing an adjusted Cox proportional hazards model for the composite renal endpoint across the quartiles of urine tubular biomarker levels, only the upper quartiles of urine cystatin-C and KIM-1 significantly predicted the composite renal endpoint. Conclusion: Urine biomarkers of tubular injury effectively identified diabetic patients at elevated risk for CKD progression and death in T2DM patients